DAMPAK BREXIT TERHADAP HUBUNGAN BILATERAL INGGRIS-IRLANDIA - Fajar Mahardika; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study explains the impact of Britain's exit from the European Union on British and Irish relations. Britain's exit from the European Union is known as Brexit. On June 23, 2016 the United Kingdom conducted a referendum which resulted in Britain leaving the European Union. After the British exit from the European Union, the UK adopted a policy of increasing security in the border area, which generated negative reactions from Ireland. So that British policy has a negative impact on relations between the two countries.             This study uses the perspective of Neorealism in international relations and the level of analysis of the Nation State is supported by Foreign Policy Theory and this study uses the Concept of National Interest. This research is a qualitative research with a documentary study research method. The scope of research is during PM Theresa May.             This study shows that the impact of Brexit on Britain and Ireland is that the UK violated an agreement with Ireland on the border and the policy received a negative response. As a result of the border also reduced the interest of tourists from the UK to Ireland and the UK also adopted a policy of imposing an increase in import export tariffs after leaving the European Union. Keywords: Brexit, United Kingdom, Ireland, Impact, Bilateral Relations